Case Report: Locking Plate for Cubitus Varus Correction in a 7-Year-Old Girl With Osteogenesis Imperfecta - Hong, Pan; Liu, Ruikang; Rai, Saroj; Li, Jin (Frontiers in Pediatrics, 2022)
Background: Cubitus varus deformity is a common complication of untreated elbow fractures in children. However, cubitus varus in osteogenesis imperfecta (OI) children is a rare but challenging situation. To the author’s knowledge, it is the first study discussing the correction of cubitus varus deformity in patient with OI. Case Presentation: Here we report a case of a 7-year-old OI girl with cubitus varus deformity due to a supracondylar fracture of humerus 3 year ago. The patient’s parent gave a history of supracondylar fracture of left humerus in 2015. Without medical intervention, the patient was admitted into our institution for corrective surgery with the diagnosis of osteogenesis imperfecta and cubitus varus deformity in the left arm. Result: Medications including calcium, vitamin D and bisphosphonates were administered before the corrective surgery of cubitus varus, and a single locking plate was used to fixate the osteotomy. Right after the surgery, the appearance and range of motion (ROM) of the left arm was almost normal. Combined with gradual rehabilitation, the ROM of the left arm was normal without pain during daily use within one-year follow up. The hardware was removed as the nailing of the forearm fractures was performed at the same time. In the latest follow-up in September, 2021, the appearance and ROM of the left arm was normal. Conclusion: Cubitus varus is a common deformity in children with elbow injuries, but it presents a challenging situation of compound fractures in OI patients. Locking plate combined with meticulous pharmacological intervention provides a good option for corrective surgery of cubitus varus in patients with OI.